Evaluation of Patients with Intracranial Tumors and Central Diabetes Insipidus. (1st October 2013) - Varan, Ali; Atas, Erman; Aydın, Burça; Yalçın, Bilgehan; Akyüz, Canan; Kutluk, Tezer; Büyükpamukçu, Münevver
<x xml:space="preserve">Abstract</x> The aim of the study is to evaluate the etiologic and clinical characteristics, treatment regimens, and outcome of the patients with intracranial tumors presenting with central diabetes insipidus (DI). Sixty-nine patients with intracranial tumors presenting with central DI between 1972 and 2012 were retrospectively evaluated. Fifty-three out of 69 patients were included in the analysis. Male/female ratio was 1.52, median age was 7.6 years. Of 53 patients, 37 patients (69.8%) were diagnosed with Langerhans cell histiocytosis, 14 patients (26.4%) with germinoma, 1 (1.9%) with astrocytoma, and 1 (1.9%) with optic glioma. 10-year overall survival (OS) rate and disease-free survival rate for all patients were 91.7% and 52%. 10-year OS rate according to diagnostic criteria was 91% for Langerhans cell histiocytosis (LCH) cases, 79% for intracranial germinoma, which was statistically significant (P = .0001). Central DI may be very important clinical presentation of serious underlying disease in children. Intracranial tumors are the most frequent cause of DI. Most frequent diagnosis were LCH and germ cell tumors in our series.